Effect of Lactobacillus plantarum KSFY01 on the exercise capacity of D-galactose-induced oxidative stress-aged mice - Chen, Qiuping; Liu, Chuannan; Zhang, Yinglong; Wang, Shuai; Li, Fang (Frontiers in Microbiology, 2022)
Objectives: Aging is a process that involves comprehensive physiological changes throughout the body, and improvements in the exercise capacity of individuals may delay aging and relieve fatigue. The purpose of this study was to investigate the effect of the probiotic Lactobacillus plantarum KSFY01 (L. plantarum KSFY01) on exercise tolerance in mice induced into a state of accelerated physiological aging by oxidative stress. Methods: A mouse model of accelerated aging was established using D-galactose. The bacteria L. plantarum KSFY01 was isolated from fermented yak yogurt. The effect of L. plantarum KSFY01 on the improvement of exercise capacity in aging-accelerated mice was evaluated by measuring their running time until exhaustion, histopathological sections, related biochemical indicators, and underlying gene expression. Results: The oral administration of L. plantarum KSFY01 prolonged the running time of mice and reduced their creatine kinase (CK), alanine aminotransferase (ALT), and aspartate aminotransferasem (AST) levels. We observed that L. plantarum KSFY01 significantly improved the exercise capacity of mice and alleviated liver damage. Treatment with L. plantarum KSFY01 reduced the blood urea nitrogen (BUN), lactic acid (LD) accumulation, and lactate dehydrogenase (LDH) elevations produced by the accelerated aging state, and also reversed the changes in muscle glycogen (MG). The results of the antioxidant indices in vivo showed that L. plantarum KSFY01 intervention increased the activity of antioxidant enzymes, and restored the balance between the oxidative and antioxidant systems in fatigued mice. By investigating the underlying molecular mechanism, our results showed that L. plantarum KSFY01 intervention significantly reversed the decline in the expression levels of nuclear factor-erythroid 2 related factor 2 (Nrf2) signaling pathway-related factors and improved the body's antioxidant capacity. We determined that the underlying molecular mechanism responsible for the antioxidant effect of L. plantarum KSFY01 mainly involves the activation of the Nrf2 pathway. The effect of L. plantarum KSFY01 was dose-dependent, and the expression level of Nrf2 increased with increasing dosage of the probiotic. Conclusion: This study demonstrated that the probiotic L. plantarum KSFY01 exerts antioxidant effects and improved the athletic ability of mice. These findings are of significance to the development and utilization of probiotic resources.